Grupos comunitários nos colegiadosescolares: entre o instituído e o realizado.A experiência de duas escolas públicasmunicipais de Belo Horizonte. - Luiz Fernando da Silva (2010)
The current research tried to investigate the impacts that the introduction of community groups (defined as community organizations, sports association, religion groups, non profitable organization (ONG), among others) brought to the school boards of the school council in the city of Belo Horizonte (RME/BH). This device is presented in the resolution number 001/2005 of the Secretaria Municipal de Educação (SMED/PBH), which among other aspects, started up two important regimentations: the parity in the representation of the workers of education, parents/mothers, students legal responsible, with 30% of seats for each one, and the community group representation, with 10% of the seats in the school board. The research was developed in two schools of the RME/BH, which were built by means of Orçamento Participativo (OP/BH) of Belo Horizonte (OP/BH), thinking that their experience in OP might facilitate the introduction of community groups in the school board and its engagement in the school management influencing its actions. This engagement of the community via community groups happened until the schools opening. However, this research revealed that this engagement was not a continuous process as time went by. The schools which were analyzed, each one in its own way, performed just parts of the resolution. The regimented parity was established reversing the majority in the number of educational workers which were predominant by then, mainly in comparison with the others, but without interfering in the school board procedures, chiefly regarding its power sharing. Regarding to the introduction of the community groups representation, it was observed that it did not exist at Barreiro school. At Nordeste School, despite of what was established in legal terms, it introduced the community representation instead of community groups representation. The linking representative/elector based on both schools, which in general, was based on sporadic and infrequent meetings with some electors based on the school shifts (work and study). It was analyzed three administrations in 2003/2004, 2005/2006, 2007/2008. Those years represent the before, during and after of the resolution published. The techniques used were: documents data, semi-structured interviews and direct observation. The collected data indicates that scheduled issues, the discussed issues and resolved issues did not change by the resolution as well as it did not change the regularity of the meetings , the frequency of the official members, the majority of record of the educational workers speaking , among other aspects. The union of the community groups that occur in order to conquer the right to have access to school, via OP , did not expand to a greater integration of these groups with the school, especially to the school management , even with the publishing of the resolution mentioned above.